Hyoid apparatus and pharynx in the lion (Panthera leo), jaguar (Panthera onca), tiger (Panthera tigris), cheetah (Acinonyx jubatus) and domestic cat (Felis silvestris f. catus) - Weissengruber, GE (Blackwell Science Inc, 2002)
Structures of the hyoid apparatus, the pharynx and their topographical positions in the lion, tiger, jaguar, cheetah and domestic cat were described in order to determine morphological differences between species or subfamilies of the Felidae. In the lion, tiger and jaguar (species of the subfamily Pantherinae) the Epihyoideum is an elastic ligament lying between the lateral pharyngeal muscles and the Musculus (M.) thyroglossus rather than a bony element like in the cheetah or the domestic cat. The M. thyroglossus was only present in the species of the Pantherinae studied. In the lion and the jaguar the Thyrohyoideum and the thyroid cartilage are connected by an elastic ligament, whereas in the tiger there is a synovial articulation. In adult individuals of the lion, tiger and jaguar the ventral end of the tympanohyal cartilage is rotated and therefore the ventral end of the attached Stylohyoideum lies caudal to the Tympanohyoideum and the cranial base. In newborn jaguars the Apparatus hyoideus shows a similar topographical position as in adult cheetahs or domestic cats. In adult Pantherinae, the Basihyoideum and the attached larynx occupy a descended position: they are situated near the cranial thoracic aperture, the pharyngeal wall and the soft palate are caudally elongated accordingly. In the Pantherinae examined the caudal end of the soft palate lies dorsal to the glottis. Differences in these morphological features between the subfamilies of the Felidae have an influence on specific structural characters of their vocalizations.